SOCIAL CONTROL AND ECONOMIC CRIME - V. I. Poklad (Russian Journal of Economics and Law)
Objective: to identify the influence of social control on counteracting the economic crimes. Methods: on basis of methodology of functionalism the abstract-logical method was used. Results: The determining influence of social standards on economic processes is proved by means of comparison of characteristics in operation of the economy as a social institution and the economy in the capacity of legal institution. For this reason the efficiency of counteracting the economic crimes depends on the conformity of prescriptions of law with social expectations. Scientific novelty: shifting the emphasis in counteracting the economic crimes from criminal-repressive techniques to value-standard regulations. Practical value: consists in correcting of methodology of state and legal management of the economy with due regard for functioning of the mechanisms of social control in the sphere of economy.